Her Job, her Safety? Domestic Violence and Women's Economic Empowerment: Evidence from Ethiopia - Fenet Jima Bedaso (Global Labor Organization (GLO), 2024)
Domestic violence against women is a pervasive public health problem in all countries regardless of cultural, economic, and political background. Yet, the prevalence of domestic violence is very high in Sub-Saharan Africa. In this paper, I examine the effect of women's employment on domestic violence using the Demographic and Health Survey in Ethiopia. To address the endogeneity of women's employment decisions due to reverse causality, the study employs an Instrumental Variables approach by exploiting exogenous geographical variation of women's employment rate at the community level. Moreover, the estimation accounts for the characteristics of socioeconomic and climate variations at the community level using external geospatial satellite information. After accounting for the endogeneity issue, the estimation result shows that women's employment significantly reduces the risk of domestic violence. This result holds robust across different dimensions of domestic violence such as physical, sexual, and emotional violence, and for urban and rural places of residence.
Keywords: J12; J16; J21; 330; Domestic violence; women employment; IV estimations; Ethiopia